PELAKSANAAN PEMBELAJARAN SENI MUSIK MENGGUNAKAN PENDEKATAN DEEP LEARNING DI KELAS VII SMP MUHAMMADIYAH 5 PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of music learning using the Deep Learning approach, the challenges faced by teachers, and the responses of students in class VII.3 at SMP Muhammadiyah 5 Padang. The study uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results show that the implementation of Deep Learning includes three aspects: meaningful learning, mindful learning, and joyful learning. Meaningful learning is carried out by connecting the material with students’ daily experiences and local culture, such as talempong and saluang, making the learning process easier to understand. Mindful learning is implemented through reflection, discussions, and learning journals, but it has not been optimal due to time limitations and passive students. Joyful learning is effectively applied through hands-on practice, group work, sound exploration, and the use of popular songs, which increase student engagement. The challenges include limited teacher understanding, inadequate facilities and infrastructure, and uneven student participation. Overall, students respond positively, although some still lack confidence during practice.